Zawyet Sultan: Second Preliminary Report. Excavation Season 2022 - Bussmann, Richard; Vanthuyne, Bart (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
Excavations in 2022 at Zawyet Sultan have revealed a cemetery of the Old Kingdom and First Intermediate Period on the desert slope south of the rock tombs (zone 5). Tombs of the early Old Kingdom include shaft tombs, rock circle tombs, and surface burials in wooden, ceramic, and mud coffins, while those of the late Old Kingdom and early First Intermediate Period include shaft tombs and a mastaba with multiple shafts. The simple surface burials are located at the lower fringe of the desert slope, the shaft tombs halfway up, and the mastaba complex at the upper end of the hillside. The spatial distribution suggests that the social hierarchy of the local community was mirrored in the vertical landscape. The area was reused in the late 18ᵗʰ Dynasty for individual burials and possibly also for other purposes.